Design, Development and Optimization of Buccal Tablet Containing Extract of Terminalia chebula Retz. for the Treatment of Asthma - Suruse, P. B.; Gawali, M. B.; Kalkotwar, R. S.; Bhabad, R. B.; Bagdane, S. B.; Barde, L. G. (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The aim of the study was to design, develop, and optimize the buccal tablets containing extract of Terminalia chebula Retz. for the treatment of asthma. Materials and Methods: Buccal tablets were made using the direct compression method, and screening tests with various polymers were run to see how they affected the properties of the tablets. The utilisation of response surface methods, two polymer types, carbopol® and HPMC, were chosen for additional optimization research. Strength of mucoadhesion and % two significant responses that the drug permeated after 8 hr from the buccal mucosa were chosen. By using a swelling index analysis, the profiles and kinetics of in vitro drug release were examined. Results: The Terminalia chebula Retz. content in buccal tablets was determined to be 99.14±0.44%, and a DSC analysis showed that there was no chemical interaction between the ingredients of the tablet (8 g carbopol 934 and 20 g HPMC K15 made up the optimal formulation). After 8 hr of in vitro dissolving studies, a cumulative Terminalia chebula Retz. release of 90% was reached, which was confirmed by swelling analysis. Conclusion: The findings suggested that Terminalia chebula Retz's. optimised buccal tablets would be a promising and different delivery method for the treatment of asthma.
Keywords: Terminalia chebula Retz.; Buccal tablet; HPMC K15; Optimization; Carbopol; DoE